Record mondial d'utilisation du coton annoncé - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Les prévisions de l'USDA pour 2002/03 pour le coton prévoient un...